AGAMA, ILMU PENGETAHUAN DAN FILSAFAT - Kurnia Muhajarah; Muhammad Nuqlir Bariklana (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
This article has the background that religion, science and philosophy have a connection. They complement and complement each other for humans in search of truth. This article tries to explore how the real connection between religion, science and philosophy is. The study will be compared to Islam, so that it will be known to what extent science and philosophy in the Islamic view of explaining science. This article is a qualitative research based on literatureresearch (library) . The results showed that scienc e, philosophy and religion have relevance to three main human potentials, namely reason, mind and feeling in order to obtain truth and human happiness